Competitive state anxiety among junior handball players - Rokka, S.; Mavridis, G.; Bebetsos, E.; Mavridis, K. (The Sport Journal, 2009)
The aim of the present study was to evaluate the levels of intensity and direction of the competitive state anxiety in junior handball players prior to a competition and to investigate any possible differences between male and female players, as well as in relation to their athletic experience. The sample of the study consisted of 115 handball players, members of eight handball teams (four male and four female), which participated in the Greek Junior Handball Championships finals held in Athens in 2008. For the data collection, the model used was the Competitive State Anxiety Inventory-II (CSAI-II, Martens, Burton, Vealey, Bump & Smith, 1983; Martens et al., 1990; Jones & Swain, 1992), which was modified for the Greek population by Stavrou, Zervas, Kakkos & Phychoudaki (1998). All players filled in the questionnaire 30 minutes before the competition. The results showed that male junior handball players reported lower scores of cognitive anxiety, which was facilitative to performance. On the other hand, females displayed a higher score in cognitive anxiety, which was rather debilitative to performance. Furthermore, junior male handball players displayed higher self-confidence, with positive effects on their performance, while female handball players stated lower self-confidence, which was neither facilitative nor debilitative to performance. In relation to years of experience, the results revealed that players with four to six years of experience showed higher self-confidence with facilitating direction, while players with less years of experience displayed lower self-confidence, with neither facilitative nor debilitative effects on their performance. In conclusion, the psychological preparation of junior handball players must be taken into serious consideration, during the coaching procedure. Nonetheless, further investigation is needed for the generalisation of the results in Greek handball.